PENINGKATAN PENDAPATAN PETANI HUTAN RAKYAT DENGAN USAHATANI TANAMAN OBAT SISTEM AGROFORESTRY DI KABUPATEN BANTUL - Triyono; Rahmawati, Nur (Jurnal Wana Tropika, 2012)
The herbal farm is comfortable with people need trend to consumpt by back to nature. This research aims to know income and profit of the herbal farm, income contribution on farmer income and feasibility of herbal farm on agroforestry system. The method used descriptif analyze by sample survey approach where is the location was defined by purpossive sampling and there are 70 sample of farmer was taken by simple random sampling. The Data was analized by using cost, income and profit analyzing. In addition it was used by return cost ratio (R/C) analyzing and income contribution analyzing. The result show that income of herbal farm is Rp. 2.255.064, - or 39 percent of total farmer income. The profit is Rp. 1.853.719,-. Based on return the cost analyzing and break event point, herbal farm is feasible and profitabel to be developed. Keywords : Herbal farm, agroforestry, income, feasible